2005
DOI: 10.1253/circj.69.301
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Regional Wall Motion Analysis Immediately After Exercise for the Detection of Single-Vessel Coronary Artery Disease

Abstract: rolonged regional myocardial dysfunction following exercise-induced ischemia has been identified as a sensitive marker of ischemia in both an experimental model 1 and patients with known coronary artery disease (CAD). [1][2][3][4] Nevertheless, the correlation between a wall motion abnormality detected by ECG-gated single-photon emission computed tomography (SPECT) and the angiographic data has not been fully evaluated. ECG-gated SPECT provides information on global as well as regional systolic function, 5,6 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
(25 reference statements)
0
38
0
Order By: Relevance
“…Additionally, multislice computed tomography and magnetic resonance imaging can be useful in the evaluation of the coronary anatomy because of their higher image resolution, complex 3-dimensional imaging and non-invasiveness. ECG-gated single-photon emission computed tomography as a non-invasive procedure provides concomitant evaluation of myocardial blood flow and cardiac functions and it is a useful tool in the diagnosis of ischaemia due to coronary anomaly [8,24]. Non-invasive tests are recommended preferably in young individuals having congenital heart disease if there is suspicion of coronary anomalies [8,24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, multislice computed tomography and magnetic resonance imaging can be useful in the evaluation of the coronary anatomy because of their higher image resolution, complex 3-dimensional imaging and non-invasiveness. ECG-gated single-photon emission computed tomography as a non-invasive procedure provides concomitant evaluation of myocardial blood flow and cardiac functions and it is a useful tool in the diagnosis of ischaemia due to coronary anomaly [8,24]. Non-invasive tests are recommended preferably in young individuals having congenital heart disease if there is suspicion of coronary anomalies [8,24].…”
Section: Discussionmentioning
confidence: 99%
“…12,13) Thus, although ECG-gated Tc-99m tetrofosmin SPECT might be a high-cost investigation, it can assess not only myocardial ischemia and viability, but also cardiac systolic and diastolic function at the same time. Study limitations: The results from the 14 patients in group C suggested the need for a larger patient population.…”
Section: Assessment Of LV Volume and Systolic Function Obtained By Qgsmentioning
confidence: 99%
“…[20][21][22] However, we found that a post-stress EF depression was not associated with adverse outcome in terms of perioperative cardiac events. This is probably because we used dipyridamole instead of exercise stress, which increases myocardial oxygen consumption and facilitates the likelihood of post-ischemic stunning.…”
Section: Discussionmentioning
confidence: 58%
“…The stress LVEF -rest LVEF value was also calculated to obtain an index reflecting post-ischemic stunning. [20][21][22] The presence of wall motion abnormality was defined as the presence of segmental hypokinesis visually diagnosed through the cine mode display of the QGS program.…”
Section: Myocardial Spect Imagingmentioning
confidence: 99%